Reduced cardiac function is associated with cardiac injury and mortality risk in hospitalized COVID‐19 Patients. Issue 12 (14th October 2020) - Chen, Lu Q.; Burdowski, Joseph; Marfatia, Ravi; Weber, Jonathan; Gliganic, Kathleen; Diaz, Nancy; Ramjattan, Neiman; Zheng, Haoyi; Mihalatos, Dennis; Wang, Lin; Barasch, Eddy; Leung, Amanda; et al.
Abstract: Background: Cardiac injury is common in COVID‐19 patients and is associated with increased mortality. However, it remains unclear if reduced cardiac function is associated with cardiac injury, and additionally if mortality risk is increased among those with reduced cardiac function in COVID‐19 patients. Hypothesis: The aim of this study was to assess cardiac function among COVID‐19 patients with and without biomarkers of cardiac injury and to determine the mortality risk associated with reduced cardiac function. Methods/Results: This retrospective cohort study analyzed 143 consecutive COVID‐19 patients who had an echocardiogram during hospitalization between March 1, 2020 and May 5, 2020. The mean age was 67 ± 16 years. Cardiac troponin‐I was available in 131 patients and an increased value (>0.03 ng/dL) was found in 59 patients (45%). Reduced cardiac function, which included reduced left or right ventricular systolic function, was found in 40 patients (28%). Reduced cardiac function was found in 18% of patients without troponin‐I elevation, 42% with mild troponin increase (0.04‐5.00 ng/dL) and 67% with significant troponin increase (>5 ng/dL). Reduced cardiac function was also present in more than half of the patients on mechanical ventilation or those deceased. The in‐hospital mortality of this cohort was 28% (N = 40). Using logistic regression analysis, we found that reduced cardiac function was associated with increased mortality with adjusted odds ratio (95% confidence interval) of 2.65 (1.18 to 5.96). Conclusions: Reduced cardiac function is highly prevalent among hospitalized COVID‐19 patients with biomarkers of myocardial injury and is independently associated with mortality.